Medulloblastoma in a patient with the PTPN11 p.Thr468Met mutation. Issue 8 (27th June 2013) - Rankin, Julia; Short, John; Turnpenny, Peter; Castle, Bruce; Hanemann, C. Oliver
ABSTRACT Medulloblastoma is the commonest brain tumor in childhood and in a minority of patients is associated with an underlying genetic disorder such as Gorlin syndrome or familial adenomatous polyposis. Increased susceptibility to certain tumors, including neuroblastoma and some hematological malignancies, is recognized in disorders caused by mutations in genes encoding components of the RAS signaling pathway which include Noonan syndrome, Noonan syndrome with multiple lentigines (NSML; formerly called LEOPARD syndrome), Costello syndrome, Cardiofaciocutaneous syndrome, Legius syndrome, and Neurofibromatosis type 1 (NF1), collectively termed RASopathies. Although an association between medulloblastoma and NF1 has been reported, this tumor has not previously been reported in other RASopathies. We present a patient with NSML caused by the recurrent PTPN11 mutation c.1403C > T (p.Thr468Met) in whom medulloblastoma was diagnosed at age 10 years. Medulloblastoma could therefore be part of the tumor spectrum associated with this disorder. © 2013 Wiley Periodicals, Inc.